2017
DOI: 10.1016/j.ejmech.2017.03.088
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro antitumour activity of crassalactone D, its stereoisomers and novel cinnamic ester derivatives

Abstract: Naturally occurring styryl lactone, crassalactone D (1), unnatural 4-epi-crassalactone D (2), and the corresponding 7-epimers (3 and 4) have been synthesized starting from d-glucose. The key step of the synthesis is a new one-pot sequence that commenced with a Z-selective Wittig olefination of suitably functionalized sugar lactols with a stabilized ylide, (methoxycarbonylmethylene)-triphenylphosphorane, in dry methanol, to afford 1 or 3, in the mixtures with the corresponding 4-epimers (2 or 4, respectively). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…The results showed that 20 constituents of DMD were found in the plasmas of MDMD‐treated rats and NMDMD‐treated rats. Furthermore, more bioactive constituents were found in plasma of MDMD‐treated rats than in NMDMD‐treated rats, and these compounds may be considered potential effective constituents in DMD because they have extensive activities, such as hydroxybenzoic acid (3), which has antioxidant activity (Siao et al, ); cinnamoyl glucose (21), which possesses antitumor and anti‐inflammatory activity (Kovacevic et al, ); benzoyloxy paeoniflorin (37), which has proven antioxidant activity (Ryu et al, ); and hydroxy physcion (57) and rhein‐8 ‐O‐ glucopyranoside (20), which have been reported to ameliorate lung inflammatory responses (Kwon et al, ). The results showed that mirabilite could influence the absorption of some bioactive constituents in DMD.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that 20 constituents of DMD were found in the plasmas of MDMD‐treated rats and NMDMD‐treated rats. Furthermore, more bioactive constituents were found in plasma of MDMD‐treated rats than in NMDMD‐treated rats, and these compounds may be considered potential effective constituents in DMD because they have extensive activities, such as hydroxybenzoic acid (3), which has antioxidant activity (Siao et al, ); cinnamoyl glucose (21), which possesses antitumor and anti‐inflammatory activity (Kovacevic et al, ); benzoyloxy paeoniflorin (37), which has proven antioxidant activity (Ryu et al, ); and hydroxy physcion (57) and rhein‐8 ‐O‐ glucopyranoside (20), which have been reported to ameliorate lung inflammatory responses (Kwon et al, ). The results showed that mirabilite could influence the absorption of some bioactive constituents in DMD.…”
Section: Resultsmentioning
confidence: 99%
“…To a cooled (0°C) and stirred solution of 12,16,11,21,23,25 or 28 (1 equiv.) in dry DMF (0.05 M) was added NaH (3.0-5.0 equiv.)…”
Section: General Procedures For the Preparation Of O-methyl Derivativementioning
confidence: 99%
“…The cell cycle analysis was carried out following a previously reported procedure. 21 Detection of apoptosis. Apoptosis of K562 cells was evaluated according to a previously reported procedure.…”
Section: General Procedures For Benzyl Deprotection (Compounds 3 and 6)mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic chemist today have an essential role to play in the development of efficient syntheses of these compounds and their analogues, to optimize the biological activity. A large number of styryl lactone derivatives have been synthesized and evaluated for their cytotoxicity against different human malignant cell lines (4)(5)(6)(7)(8)(9)(10). Many of the synthesized styryl lactones exhibited strong citotoxic activity.…”
Section: Introductionmentioning
confidence: 99%